2021
DOI: 10.37897/rmj.2021.s5.19
|View full text |Cite
|
Sign up to set email alerts
|

Use of lung ultrasound and and aEEG patterns to predict the need for mechanical ventilation and the readiness for extubation in neonates with respiratory distress

Abstract: Objective. The aim of the study was to establish if lung ultrasound findings could anticipate the need for intubation and mechanical ventilation in neonates with respiratory distress and if lung ultrasound and aEEG criteria could be used in appreciation of the readiness for extubation of the neonatal patients resulting in a decrease of the rate of extubation failure. Material and method. There were analyzed the cases of 50 late preterm and early term neonates presenting with respiratory distress. Lung ultrasou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(19 citation statements)
references
References 0 publications
2
17
0
Order By: Relevance
“…20,21 Moreover, recent studies have indicated that LU is a promising tool for prediction of extubation outcomes (success or failure) in neonates. [22][23][24][25][26][27][28][29] These recent findings in neonates are consistent with recent systematic review in adults which concluded that LU can assist in determining the ideal time for extubation. 30 To the best of our knowledge, there has been no systematic evaluation of the diagnostic accuracy of neonatal LU score (LUS) in predicting extubation failure.…”
Section: Introductionsupporting
confidence: 85%
See 4 more Smart Citations
“…20,21 Moreover, recent studies have indicated that LU is a promising tool for prediction of extubation outcomes (success or failure) in neonates. [22][23][24][25][26][27][28][29] These recent findings in neonates are consistent with recent systematic review in adults which concluded that LU can assist in determining the ideal time for extubation. 30 To the best of our knowledge, there has been no systematic evaluation of the diagnostic accuracy of neonatal LU score (LUS) in predicting extubation failure.…”
Section: Introductionsupporting
confidence: 85%
“…Out of the eight included studies, radiologists conducted LU scans in three studies, 22,23,28 while pediatricians/neonatologists performed the scans in the remaining studies. Quantitative assessment of LU scans, in which a score was given, was conducted in seven studies, whereas one study performed a qualitative assessment 25 . The quantitative scores varied across studies, with a total of 18 points in two studies, 23,24 24 points in one study, 29 36 points in three studies, 22,26,27 and 70 points in one study 28 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations